Customer satisfaction towards operation counter services at Amanah Saham Nasional Berhad, Melaka Branch / Kamarul Farid Kassim - Kassim, Kamarul Farid (Faculty of Business and Management, 2010)
This is a study on the customer satisfaction towards operation of counter service at ASNB, Melaka branches. Counter services is a first or front place that customer should faces to get services. In this study, it will discuss on how the quality of counter service will give impacts on the customer’s satisfaction during the process of service delivery. The target service firm that suggested for this study is Amanah Saham Nasional Berhad, Melaka branch and the suggested sample size for respondents are 30 respondents. The study is to identify the relationship between service quality dimension and customer satisfaction of service provided by ASNB Melaka. Quality of service is based on their customer perception toward the actual service. Service quality dimension that will be focus through the research are tangibility, reliability, responsiveness, empathy and assurance. There are lots of suggestions from this study and might be useful for future improvement.